Work-based learning: How it changes leadership - Joseph A. Raelin (Development and Learning in Organizations, 2011)
Purpose Although readers of this journal are familiar with work-based learning and with leadership, they may not have entertained the link between them. The paper aims to contend that the link is that the former changes the latter. The authentic practice of work-based learning produces a more collective form of leadership, matching the former's founding principles and practices. Design/methodology/approach Guided by the author's long-standing research of both work-based learning and leadership, he searches for commonalities in their underlying conditions, proposing a means to identify their relationship. The author's model invites both further study by researchers and field replication by practitioners. Findings A number of compatible principles and practices undergird the fields of work-based learning and collective leadership; namely, their mutual commitment to dialogic processes based on nonjudgmental inquiry; their accentuation of the state of genuine curiosity - even doubt; their acceptance of critical challenge; and their willingness to disturb preconceived world views on behalf of a common good. Practical implications Managers and executives taking advantage of work-based learning, when offered as an authentic practice, may acknowledge its powerful impact on leadership, but as in the case of learning, they must be willing to sustain its collaborative nature to release its potential. Social implications When people in a community or organization authentically share leadership, it ignites their natural talent to contribute to the growth of that community and it also elevates the value of trust by bringing genuineness to the community. Originality/value Practitioners in the development and learning field already know the value of work-based learning for learning purposes, but in this article, it is shown to impact leadership in a profound way - it changes it. As a collective and reflective practice, it responds to contemporary needs to find ways to release people to contribute their natural talents on behalf of mutual action.
Keywords: J24; M53; M51; M12; J28; 330; Leaderful practice; Work-based learning; Collective leadership; Leadership; Shared leadership; Workplace learning